Comparative Analysis of Liquefied Natural Gas (LNG) Distribution Scheme using Milk-Run and Hub-Spoke Methods on Small-Scale LNG Carrier in Eastern Indonesia - Muzhoffar, Dimas Angga Fakhri; Auzani, Ahmad Syihan; Altaf, Ahmad Nur; Putra, Aleg Restu Pridana; Wahyono, Condro Baskoro Jati (LPPM AKMI SUAKA BAHARI CIREBON, 2024)
Liquefied Natural Gas (LNG) has been seen as a promising alternative in the face of these challenges. However, attention remains focused on the efficiency of LNG distribution, especially in the face of unpredictable demand fluctuations. Currently, with demands for increasing distribution efficiency, Indonesia, one of the largest LNG producers in Southeast Asia, faces a particular challenge in achieving efficiency in meeting domestic energy needs. To address the problem, the Indonesian government has initiated a program to streamline energy infrastructure development, focusing on LNG distribution in Eastern Indonesia. The study will use two distribution schemes, Milk-Run and Hub-Spoke, with different types of ship capacity to calculate operating costs. This study focuses on comparing the effectiveness of the two popular distribution schemes, the Milk-Run and the Hub-Spoke, especially in optimizing LNG distribution in the area. The data in this study was obtained from institutions that openly publish data in a digital system. The findings suggest that the Milk-Run distribution scheme was identified as an optimal solution for LNG delivery to multiple points from a single source for Northern and Southern Papua. The results of this study are expected to provide practical guidance to the parties concerned in their efforts to improve the efficiency of LNG distribution in eastern Indonesia and further study in other regions of Indonesia.